FAKTOR - FAKTOR YANG BERPENGARUH TERHADAP FRAUDULENT FINANCIAL REPORTING DENGAN MENGGUNAKAN ANALISIS FRAUD PENTAGON - Hanifah Agusputri; Sofie Sofie (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2019)
This research aimed to analysis the effect of fraud pentagon, the variable are pressure (financial targets, financial stability and external pressure), opportunity (ineffective monitoring and nature of industry), rationalization (change in auditor and rationalization), competence (change of directors) and arrogance (frequent number of CEO’s picture) to fraudulent financial reporting which measured using F-Score Model. This research used secondary data and purposive sampling method, there were 201 industrial manufacture industries that were registered in Indonesia Stock Exchange in period of 2015-2017 as research sample. This research used logistic regression analysis by using data processing application of SPSS. The result showed that financial target and ineffective monitoring have a positive affect on the  fraudulent financial reporting. Furthermore, external pressure, nature of industry, change in auditor and rationalization have a negative affect on  fraudulent financial reporting. While, financial stability, change in directors and frequent number of CEO’s picture have not affected on  fraudulent financial reporting.